PENGARUH SIKAP, NORMA SUBJEKTIF, KONTROL PERILAKU PERSEPSIAN, PERSEPSI RISIKO, PERSEPSI KEBERMANFAATAN TERHADAP NIAT PENGGUNAAN KARTU KREDIT - Rochmawati, Sari; Purnomosidhi, Bambang (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
This study aims to examine the factors that influence intention to using credit card. This reasearch using Theory of Planned Behavior (TPB) model with external factor perceived risk and perceived benefit. This research was conducted to PNS at Brawijaya University in Malang City. This study received 81 responses of people who ever using credit card. The result of analysis for this models shows that subjective norm, perceived risk, and perceived benefit affect the intention to use credit card. Attitude and perceived behavioral control did not affect intention individual to use credit card. This research have implication for academician and bank management which is subjective norm, perceived risk, and perceived benefit affect intention persons in the area of information system card based. Keywords : intention, credit card, attitude, subjective norm, perceived behavioral control, perceived risk, perceived benefit.